Pengaruh Ketersediaan Fasilitas Pada Ruang Tunggu Terhadap Kepuasan Penumpang di Bandar Udara Sultan Mahmud Badaruddin II Palembang (International Forum of Researchers and Lecturers, 2024)
Transportation is a service system in which vehicles and infrastructure are used by the community to facilitate travel between cities and countries. One of the modes of transportation at this time that is developing is air transportation. In the changing transportation industry, there is also a need to maintain, develop and provide airport transportation facilities. With the provision of these facilities, passengers are expected to feel comfortable and safe when traveling by plane. Therefore, airport facilities have now been improved with free wi-fi specifically for air transportation service users so that passengers feel comfortable while waiting for the plane to arrive at the airport lounge. Room temperatures that are too hot or too cold can cause interference. A hot or humid room can cause a psychological reaction in humans. The purpose of this study is to determine the effect of the availability of facilities in the waiting room on passenger satisfaction and to determine how much influence the availability of facilities in the waiting room on passenger satisfaction. The research method that the researchers used in this study is a quantitative method whose processing was tested using the SPSS Version 26 application. Some of these tests include descriptive analysis, simple classical assumptions, coefficients of determination, and hypotheses. Based on the results of the test carried out, a significance test value of 0.000 < 0.05 was obtained and a calculated t value of 16,273 > t table of 1,660 so that it can be said that Ha was accepted and Ho was rejected. Judging from the R square value of 0.730, which means that the variable availability of waiting room facilities (X) affects the variable of passenger satisfaction (Y) at Sultan Mahmud Badaruddin II Airport Palembang by 73.0%.